Generational business - Mumbai Archive Project Team (Jio Institute, 2024)
Many shops in the vicinity of Mumba Devi Temple have been in business for generations. For example, Ram Jagannath Jaipurwale has been selling sweets and puja ingredients to pilgrims for three generations.